THE PHONOLOGY OF RONGGA LANGUAGE: A TRANSFORMATIONAL GENERATIVE STUDY - I NYOMAN SUPARSA (Program Magister Linguistik Universitas Udayana, 2008)
ABSTRACT Ph.D. thesis entitled “The Phonology of Rongga Language: A Transformational Generative Study” has the aims to answer three problems, including (1) How is the phonological realization of Rongga morphemes, both in phonemic and phonetic levels, (2) what are the requirements to the morphemic structure of Rongga language, both in the relation of the positive requirements and ‘if – then’ conditions?, and (3) How is the process and the phonological rules of Rongga language in order to explain the alteration from the phonological to phonetic realization? By using the Generative Phonology approach and Phonetics, in particular Articulatory and Acoustic Phonetics, Autosegmental Phonology and field-work linguistic method, a library research and analysis, and it is also supported by recording technique, note-taking, and palatographic technique, the current researchproject can be realised in the form of dissertation. Rongga language has six vowels both phonemically and phonetically including /i, e, u, o, ?, a/ [i, e, u, o, ?, a]. Phonemically Rongga language has 25 consonants they are /p, b, t, d, k, g, dZ, ?, ?, ?, ?b,